2019
DOI: 10.1093/jas/skz009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation ofBrassica carinatameal on ruminant metabolism and apparent total tract digestibility of nutrients in beef steers1,2

Abstract: Brassica carinata is a new oilseed crop with the potential of producing high-quality jet biofuel. A high-protein meal (~40% crude protein) is obtained as a byproduct of hexane-solvent oil extraction; however, limited research is available on the use of this meal as a protein supplement for beef cattle. A duplicated 4 × 4 Latin square design was used to determine the effects of supplementation with B. carinata meal on ruminal fermentation, digestibility, and blood metabolites in beef cattle consuming bahiagrass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The Association of American Feed Control Officials (AAFCO) recommends that meals containing glucosinolates should not be fed at more than 10% DM [74]; therefore, the inclusion level of CRM follows the same restriction. Studies using CRM for dairy or beef cattle are still scarce, and to our knowledge there are only three published studies [68,78,79]. Rodriguez-Hernandez and Anderson [68] determined the effects of feeding CRM to dairy heifers on growth, ruminal fermentation, and nutrient utilization.…”
Section: Dietary Inclusion and Effects On Dry Matter Intakementioning
confidence: 99%
See 4 more Smart Citations
“…The Association of American Feed Control Officials (AAFCO) recommends that meals containing glucosinolates should not be fed at more than 10% DM [74]; therefore, the inclusion level of CRM follows the same restriction. Studies using CRM for dairy or beef cattle are still scarce, and to our knowledge there are only three published studies [68,78,79]. Rodriguez-Hernandez and Anderson [68] determined the effects of feeding CRM to dairy heifers on growth, ruminal fermentation, and nutrient utilization.…”
Section: Dietary Inclusion and Effects On Dry Matter Intakementioning
confidence: 99%
“…In an experiment carried out over two consecutive years [78], eight steers were used in a duplicated 4 × 4 Latin square and fed 1.39 kg/d of CRM (approximately 0.3% BW). Authors reported that there were no effects on DMI for steers fed CRM compared to steers fed either CSM, DDGS, or SBM.…”
Section: Dietary Inclusion and Effects On Dry Matter Intakementioning
confidence: 99%
See 3 more Smart Citations